Empagliflozin Attenuates Non-Alcoholic Fatty Liver Disease (NAFLD) in High Fat Diet Fed ApoE((-/-)) Mice by Activating Autophagy and Reducing ER Stress and Apoptosis - Nasiri-Ansari, Narjes (Int J Mol Sci, 2021)
Aims/hypothesis: SGLT-2 inhibitors (SGLT-2i) have been studied as potential treatments against NAFLD, showing varying beneficial effects. The molecular mechanisms mediating these effects have not been fully clarified. Herein, we investigated the impact of empagliflozin on NAFLD, focusing particularly on ER stress, autophagy and apoptosis. Methods: Five-week old ApoE((-/-)) mice were switched from normal to a high-fat diet (HFD). After five weeks, mice were randomly allocated into a control group (HFD + vehicle) and Empa group (HFD + empagliflozin 10 mg/kg/day) for five weeks. At the end of treatment, histomorphometric analysis was performed in liver, mRNA levels of Fasn, Screbp-1, Scd-1, Ppar-γ, Pck-1, Mcp-1, Tnf-α, Il-6, F4/80, Atf4, Elf2α, Chop, Grp78, Grp94, Χbp1, Ire1α, Atf6, mTor, Lc3b, Beclin-1, P62, Bcl-2 and Bax were measured by qRT-PCR, and protein levels of p-EIF2α, EIF2a, CHOP, LC3II, P62, BECLIN-1 and cleaved CASPASE-8 were assessed by immunoblotting. Results: Empagliflozin-treated mice exhibited reduced fasting glucose, total cholesterol and triglyceride serum levels, as well as decreased NAFLD activity score, decreased expression of lipogenic enzymes (Fasn, Screbp-1c and Pck-1) and inflammatory molecules (Mcp-1 and F4/80), compared to the Control group. Empagliflozin significantly decreased the expression of ER stress molecules Grp78, Ire1α, Xbp1, Elf2α, Atf4, Atf6, Chop, P62(Sqstm1) and Grp94; whilst activating autophagy via increased AMPK phosphorylation, decreased mTOR and increased LC3B expression. Finally, empagliflozin increased the Bcl2/Bax ratio and inhibited CASPASE-8 cleavage, reducing liver cell apoptosis. Immunoblotting analysis confirmed the qPCR results. Conclusion: These novel findings indicate that empagliflozin treatment for five weeks attenuates NAFLD progression in ApoE((-/-)) mice by promoting autophagy, reducing ER stress and inhibiting hepatic apoptosis.